Pediatric pleural effusions: etiological evaluation in 492 patients over 29 years - Ütine, G. Eda; Özçelik, Uğur; Kiper, Nural; Doğru, Deniz; Yalçın, Ebru; Çobanoğlu, Nazan; Pekcan, Sevgi; Kara, Ateş; Cengiz, A. Bülent; Ceyhan, Mehmet; Seçmeer, Gülten; Göçmen, Ayhan (The Turkish Journal of Pediatrics, 2009)
Pediatric pleural effusions present a changing profile over time, both in terms of etiological subgroups and causative microorganisms in parapneumonic effusions. This retrospective study aimed to review pediatric pleural effusions in a large cohort over a 29-year period, with special emphasis on the etiological subgroups and microbiological causes of parapneumonic effusions. The medical records of 492 pediatric patients were reviewed for a comparison of subgroups of pleural effusions and microbiological causes of parapneumonic effusions between three decades. Parapneumonic effusions (381 patients) made up 77.4% of the group. Tuberculous pleurisy decreased, but malignant effusions doubled in number over time. A causative microorganism was identified in 34.6% overall, with Staphylococcus aureus and Streptococcus pneumoniae being the two most common. Relative frequency of S. aureus decreased, whereas pneumococci and Haemophilus influenzae were more frequent in recent years.